Reflectance-based detection for long term environmental monitoring. Issue 6 (June 2017) - Johnson, Brandy J.; Malanoski, Anthony P.; Erickson, Jeffrey S.; Liu, Ray; Remenapp, Allison R.; Stenger, David A.; Moore, Martin H.
Abstract: Here, the potential of colorimetric sensors utilizing porphyrin indicators for long term environmental monitoring is demonstrated. Prototype devices based on commercial color sensing chips (six per device) were combined with in-house developed algorithms for data analysis. The devices are intended to provide real-time sensing of threats. An initial outdoor data set was collected using prototype devices with occasional spiked exposure to targets. This data was supported by similar data collected in a controlled indoor environment. Weaknesses in the noted performance of the devices during these experiments were addressed through altering device parameters, algorithm parameters, and array element composition. Additional outdoor data sets totaling 1, 616 h and indoor data sets totaling 728 h were collected in support of assessing these changes to the system configuration. The optimized system provided receiver operating characteristics (ROC) of specificity 0.97 and sensitivity 1.0.